Rare bird documentation form for Greater Scaup at Lake Macbride, 1980 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1980)
Rare bird documentation form for two Greater Scaups at Lake Macbride in Johnson County, IA on April 5, 1980. Epson - sheet feed